Utilization of mensiang (Actinoscorpus grosus L.) as a cellulose-rich material for furfural synthesis - Fransiska Angelina G Rezekinta; Anwar Kasim; Novizar Nazir; F Failisnur (Institution for Industrial Research and Standardization of Industry - Padang, 2021)
The cellulose content of mensiang varies from 22% in the flower to 33% in the root. This could be used as a starting point for furfural synthesis. To separate furfural, several conditions are set for the distillation and evaporation processes. The conditions were rootstock part (A), upper stem part (B), whole stem part (C), whole stem with flowers part (D), and whole stem, flowers, and root part (E). Furfural content in the mensiang plant was conducted using Gas Chromatography-Mass Spectroscopy (GCMS) for the highest yield 11.78%, D treatment. Furfural synthesized from the mensiang plant has a furfural content of 96%. Furfural's density was 1.160 g/ml, boiling point was 161 oC, refractive index was 1.5120 obrix, and its viscosity was 1.46 cp.